Binder composition for secondary battery and electrode mixture for secondary battery containing the same

A core-shell structured binder composition addresses adhesion and contamination issues in secondary batteries, improving electrode integrity and productivity by enhancing adhesion and reducing surface defects.

JP2025503070AActive Publication Date: 2025-01-30LG CHEM LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024543250
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-04-12
Filing Date
2023-04-12
Publication Date
2025-01-30
Estimated Expiration
2043-04-12

AI Technical Summary

Technical Problem

Existing secondary batteries face issues with electrode adhesion and surface contamination during the pressing process, leading to decreased battery performance and life due to the loosening of bonds between electrode active materials and collectors, especially when using materials with high volume expansion like silicon or silicon-lithium alloys.

Method used

A core-shell structured binder composition is used, comprising emulsified polymer particles with specific particle size and glass transition temperature ratios, which enhances adhesion and reduces contamination by adsorbing roll contaminants during the press process.

Benefits of technology

The binder composition improves electrode adhesion and reduces surface defects, thereby enhancing the productivity and lifespan of secondary batteries by maintaining electrode integrity and reducing roll contamination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025503070000001
    Figure 2025503070000001
  • Figure 2025503070000002
    Figure 2025503070000002
  • Figure 2025503070000003
    Figure 2025503070000003
Patent Text Reader

Abstract

The present invention relates to a binder composition for a secondary battery, which contains emulsion polymer particles A having a core-shell structure including a core part and a shell part occupying part or all of the surface of the core part, and emulsion polymer particles B having no core-shell structure, and satisfies the following [Relational Expression 1]. [Relational Expression 1] 50 < N(A) / N(B) < 400 (In the formula, N(A) is the number of particles of the emulsion polymer particles A having the core-shell structure, and N(B) is the number of particles of the emulsion polymer particles B having no core-shell structure.)
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a binder composition for a secondary battery, an electrode mixture for a secondary battery containing the same, and a secondary battery. [Background technology]

[0002] In recent years, with technological development and increasing demand for portable devices such as portable computers, mobile phones, and cameras, the demand for secondary batteries as energy sources has been rapidly increasing. Among such secondary batteries, lithium secondary batteries, which exhibit high energy density and working potential, long cycle life, and low self-discharge rate, have been actively researched and are now commercially available and in wide use.

[0003] Generally, among secondary batteries, lithium secondary batteries are charged and discharged by repeatedly inserting and extracting lithium ions from the positive electrode into and from the negative electrode. This repeated insertion and extraction of lithium ions loosens the bonds between the electrode active material or conductive material, increasing the contact resistance between the particles. As a result, the ohmic resistance of the electrode increases, causing a decrease in battery characteristics. Therefore, the binder needs to act as a buffer against the expansion and contraction of the electrode active material due to the insertion and extraction of lithium ions in the electrode, and is therefore preferably an elastic polymer.

[0004] In addition, the binder must have enough adhesive strength to maintain the binding force between the electrode active material and the current collector during the drying process of the electrode plate.In particular, when natural graphite, which has a theoretical discharge capacity of 372mAh / g, is combined with materials with large discharge capacity such as silicon, tin, and silicon-tin alloys, the volume expansion of the material increases significantly as charging and discharging proceeds, which causes the anode material to separate, resulting in a rapid decrease in battery capacity with repeated cycles.

[0005] Therefore, there is a strong demand in the industry for research into binders and electrode materials that can prevent separation between electrode active materials or between the electrode active material and the current collector during electrode production, and that can control the volumetric expansion of the electrode active material that occurs during repeated charging and discharging due to their excellent physical properties, thereby improving the structural stability of the electrode and thereby the performance of the battery even after hundreds of cycles.

[0006] Furthermore, since the binder itself can act as a resistor, the binder itself must not significantly affect the resistance and ion conductivity characteristics. Since many medium- and large-sized batteries require high output, resistance is one of the important physical properties of the battery, and there is a strong demand for research into binders with low resistance. Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a binder for secondary batteries that can reduce contamination during pressing of secondary battery electrodes to improve electrode productivity, ensure high adhesive strength even during high-speed coating, and ultimately contribute to ensuring the life of secondary batteries.

[0008] Another object of the present invention is to provide a binder for secondary batteries that can eliminate the problem of electrode surface defects caused by roll contamination (a phenomenon in which electrode active materials, conductive materials, etc. are adsorbed to the roll and contaminate the roll surface) that occurs during the pressing process by inducing sufficient distribution of the binder on the electrode surface of the secondary battery. [Means for solving the problem]

[0009] The binder composition for a secondary battery according to one embodiment of the present invention comprises emulsion polymer particles A having a core-shell structure including a core portion and a shell portion occupying a part or all of the surface of the core portion, and emulsion polymer particles B having no core-shell structure, and satisfies the following [Relational Formula 1].

[0010] [Equation 1] 50 <N(A) / N(B)<400

[0011] In the above [Relationship 1], N(A) is the number of emulsion polymer particles A having the core-shell structure, and N(B) is the number of emulsion polymer particles B not having the core-shell structure.

[0012] In the above [Relationship 1], N(A) / N(B) is determined by the following [Relationship 2].

[0013] [Equation 2] N(A) / N(B)={D(B) / D(A)} 3 *{X(A) / X(B)}

[0014] In the above [Relationship 2], D(A) is the average particle size (D50) of particle A, D(B) is the average particle size (D50) of particle B, and X(A) / X(B) is the mixing ratio of A to B.

[0015] As a more preferred example, the emulsion polymer particles A having the core-shell structure have an average particle size (D50) of 100 nm or less.

[0016] As a more preferred example, all of the polymer particles contained in the binder composition for a secondary battery have an average particle size (D50) of 400 nm or less.

[0017] As a more preferred example, the glass transition temperature (Tg) of the emulsion polymer particle A having the core-shell structure is lower than 0°C.

[0018] As a more preferred example, the glass transition temperature (Tg) of the emulsion polymer particle B having no core-shell structure is lower than 0°C.

[0019] As a more preferred example, the core portion of the emulsion polymer particle A having the core-shell structure includes a polymer of one or more monomers selected from the group consisting of (group A) conjugated diene monomers or conjugated diene polymers, (group B) acrylate monomers, vinyl monomers, (meth)acrylamide monomers, and nitrile monomers, and (group C) unsaturated carboxylic acid monomers.

[0020] As a more preferred example, the core portion of the emulsion polymer particle A having the above-mentioned core-shell structure contains a polymer of monomers or polymers in which the above-mentioned (group A) monomer or polymer is contained in an amount of 30 to 70% by weight, the above-mentioned (group B) monomer is contained in an amount of 20 to 50% by weight, and the above-mentioned (group C) unsaturated carboxylic acid monomer is contained in an amount of 0.5 to 20% by weight, based on the total weight of the core portion.

[0021] As a more preferred example, the core portion of the emulsion polymer particle A having the above-mentioned core-shell structure contains styrene-butadiene latex.

[0022] As a more preferred example, the shell portion of the emulsion polymer particle A having the above-mentioned core-shell structure contains a polymer of one or more monomers selected from the group consisting of (group A) (meth)acrylic acid ester monomers, (group B) acrylate monomers, vinyl monomers, (meth)acrylamide monomers, and nitrile monomers, and (group C) unsaturated carboxylic acid monomers.

[0023] As a more preferred example, the shell portion of the emulsion polymer particle A having the above-mentioned core-shell structure contains a polymer of monomers in which the above-mentioned (group A) monomer is contained in an amount of 50 to 90% by weight, the above-mentioned (group B) monomer is contained in an amount of 0.5 to 30% by weight, and the above-mentioned (group C) unsaturated carboxylic acid monomer is contained in an amount of 0.5 to 20% by weight, based on the total weight of the shell portion.

[0024] An electrode mixture for a secondary battery according to an embodiment of the present invention includes the binder composition for a secondary battery.

[0025] A secondary battery according to an embodiment of the present invention includes the electrode mixture for a secondary battery. Effect of the Invention

[0026] According to the present invention, it is possible to provide a binder for secondary batteries that can reduce contamination during pressing of secondary battery electrodes, improve electrode productivity, ensure high adhesive strength even during high-speed coating, and ultimately contribute to ensuring the life of secondary batteries.

[0027] In addition, according to the present invention, it is possible to provide a binder for secondary batteries that can solve the problem of electrode surface defects caused by roll contamination (a phenomenon in which an electrode active material, a conductive material, etc. is adsorbed onto a roll and contaminates the roll surface) that occurs during a pressing process by inducing a sufficient distribution of the binder on the surface of a secondary battery electrode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] The term "comprising" as used herein should be understood as an open-ended term that encompasses the possibility of including other embodiments.

[0029] As used herein, the words "preferred" and "preferably" refer to embodiments of the invention that provide certain benefits, under certain circumstances. However, there may be other preferred embodiments, under the same or different circumstances. Furthermore, the recitation of one or more preferred embodiments does not imply that other embodiments are not useful, or is not intended to exclude other embodiments from the scope of the invention.

[0030] A binder composition for a secondary battery according to one embodiment of the present invention includes emulsion polymer particles A having a core-shell structure including a core portion and a shell portion occupying a part or the entirety of the surface of the core portion.

[0031] In the present invention, the core-shell structure means that the core and shell of a particle are different in composition, structure, properties, or the like.

[0032] As an example, the weight ratio of the core part to the shell part may be 95:5 to 5:95, specifically 90:10 to 10:90, more specifically 90:10 to 30:70, and even more specifically 90:10 to 50:50. The above weight ratio is a ratio for the binder according to the present invention to exhibit optimal adhesive strength, and if it is out of the above range, the intended effect of the present invention cannot be exhibited, which is not preferable.

[0033] In the present invention, the emulsion polymer particles refer to polymer particles polymerized by emulsion polymerization in the presence of an emulsifier and a polymerization initiator, and can be produced by a well-known emulsion polymerization method.

[0034] For example, the polymerization temperature and polymerization time can be appropriately set depending on the case. For example, the polymerization temperature may be about 10° C. to about 95° C., and the polymerization time may be about 0.5 hours to about 20 hours.

[0035] For example, emulsifiers that can be used in the emulsion polymerization include, but are not limited to, one or more emulsifiers selected from the group consisting of anionic emulsifiers, cationic emulsifiers, and nonionic emulsifiers. Such emulsifiers are substances that simultaneously have hydrophilic and hydrophobic groups, and form a micelle structure during the emulsion polymerization process, allowing polymerization of each monomer to occur within the micelle structure.

[0036] As an example, a polymerization initiator that can be used in the emulsion polymerization includes inorganic or organic peroxides. For example, water-soluble initiators such as potassium persulfate, sodium persulfate, and ammonium persulfate, and oil-soluble initiators such as cumene hydroperoxide and benzoyl peroxide can be used, but are not limited to these.

[0037] For example, an activator may be further included to promote the initiation of the peroxide reaction together with the polymerization initiator. Examples of such activators include, but are not limited to, one or more selected from the group consisting of sodium formaldehyde sulfoxylate, sodium ethylenediaminetetraacetate, ferrous sulfate, and dextrose.

[0038] When the polymer particles other than the emulsion polymer particles A having the core-shell structure among all the polymer particles contained in the binder composition for a secondary battery according to one embodiment of the present invention are defined as polymer particles B, the binder composition for a secondary battery according to one embodiment of the present invention contains polymer particles B. That is, the binder composition for a secondary battery contains polymer particles B not having a core-shell structure.

[0039] The binder composition for a secondary battery of the present invention contains emulsion polymer particles A having a core-shell structure and polymer particles B not having a core-shell structure, and thereby can exhibit the optimum effect aimed at in the present invention.

[0040] As a more preferred example, the polymer particles B may be emulsion polymer particles.

[0041] When N(A) is the number of emulsion polymer particles A having a core-shell structure and N(B) is the number of emulsion polymer particles B not having a core-shell structure, the binder composition for a secondary battery satisfies the following [Relationship 1].

[0042] [Equation 1] 50 <N(A) / N(B)<400

[0043] More preferably, the lower limit of N(A) / N(B) may be 100.

[0044] More preferably, the upper limit of N(A) / N(B) may be 300.

[0045] As will be confirmed from the experimental examples described below, the present invention can exhibit the optimum effects aimed at in the present invention within the above-mentioned numerical ranges.

[0046] As a more preferred example, the emulsion polymer particles A having the core-shell structure may have an average particle size (D50) of preferably 100 nm or less, more preferably 90 nm or less, and even more preferably 80 nm or less. As will be confirmed from the experimental examples described later, the present invention can exhibit the optimum effect aimed at in the present invention within the above numerical range.

[0047] As a more preferred example, all of the polymer particles contained in the binder composition for secondary batteries may have an average particle size (D50) of preferably 400 nm or less, more preferably 300 nm or less. As will be confirmed from the experimental examples described later, the present invention can exhibit the best effects aimed at in the present invention within the above numerical range.

[0048] In the present invention, when the emulsion polymer particles A and / or the polymer particles B having the core-shell structure are emulsion polymers, the average particle size (D50) of the polymer particles B can be adjusted by the amount of emulsifier, and generally, as the amount of emulsifier increases, the particle size tends to become smaller, and as the amount of emulsifier decreases, the particle size tends to become larger. The desired average particle size can be achieved by adjusting the amount of emulsifier used in consideration of the desired particle size, reaction time, reaction stability, etc.

[0049] As a more preferred example, the glass transition temperature (Tg) of the emulsion polymer particle A having the core-shell structure may be less than 0° C., less than −5° C., less than −10° C., or less than −15° C. As will be confirmed from the experimental examples described later, the present invention can exhibit the optimum effects aimed at in the present invention within the above numerical ranges.

[0050] As a more preferred example, the glass transition temperature (Tg) of the emulsion polymer particle B not having a core-shell structure may be less than 0° C., less than −5° C., or less than −10° C. As will be confirmed from the experimental examples described later, the present invention can exhibit the optimum effects aimed at in the present invention within the above numerical ranges.

[0051] As a more preferred example, the gel content of the emulsion polymer particles A having a core-shell structure and / or the emulsion polymer particles B not having a core-shell structure is preferably 95% or more. More preferably, the gel content of the emulsion polymer particles A having a core-shell structure and / or the emulsion polymer particles B not having a core-shell structure may be 95 to 99%, 95 to 98%, or 96 to 97.5%. When the gel content of the emulsion polymer particles A having a core-shell structure and / or the emulsion polymer particles B not having a core-shell structure is less than 95%, swelling in the electrolyte solution becomes large, which may shorten the life of the battery.

[0052] The gel content is calculated by the following mathematical formula 1.

[0053] [Mathematical formula 1] Gel content (%) = M b / M a *100

[0054] In the above [mathematical formula 1], M a is the weight of a sample of emulsion polymer particles measured after drying at 80°C for 24 hours, and M b is the mesh and the weight of the emulsion polymer particles remaining on the mesh after immersing a weighed sample of emulsion polymer particles in 50 g of THF (tetrahydrofuran) for 24 hours or more and sieving it through a 200 mesh sieve.

[0055] The gel content of such emulsion polymer particles indicates the degree of crosslinking of the copolymer, and is calculated according to the above [Equation 1] and is expressed as the insoluble content in the electrolyte.

[0056] As a more preferred example, the core portion of the emulsion polymer particle A having the core-shell structure may contain one or more monomers selected from the group consisting of (group A) conjugated diene monomers or conjugated diene polymers, (group B) acrylate monomers, vinyl monomers, (meth)acrylamide monomers, and nitrile monomers, and (group C) unsaturated carboxylic acid monomers or polymers.

[0057] The (group A) conjugated diene monomer may be, for example, one or more monomers selected from the group consisting of 1,3-butadiene, isoprene, chloroprene, and pyreridene, but is not limited thereto.

[0058] Examples of the conjugated diene polymer include, but are not limited to, a polymer of two or more monomers selected from the group consisting of 1,3-butadiene, isoprene, chloroprene, and pyreridene, a styrene-butadiene copolymer, an acrylonitrile-butadiene copolymer, a styrene-isoprene copolymer, an acrylate-butadiene rubber, an acrylonitrile-butadiene-styrene rubber, an ethylene-propylene-diene polymer, a polymer obtained by partially hydrogenating, epoxidizing, or brominating these polymers, and a mixture thereof.

[0059] In the above (Group B), examples of the acrylate monomer include, but are not limited to, one or more monomers selected from the group consisting of methacryloyloxyethylethyleneurea, β-carboxyethyl acrylate, aliphatic monoacrylate, dipropylene diacrylate, ditrimethylolpropane tetraacrylate, dipentaerythritol hexaacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, and glycidyl methacrylate.

[0060] The vinyl monomer may be, for example, one or more monomers selected from the group consisting of styrene, α-methylstyrene, β-methylstyrene, pt-butylstyrene, and divinylbenzene, but is not limited thereto.

[0061] Examples of the (meth)acrylamide monomer include, but are not limited to, one or more monomers selected from the group consisting of acrylamide, n-methylol acrylamide, n-butoxymethyl acrylamide, methacrylamide, n-methylol methacrylamide, and n-butoxymethyl methacrylamide.

[0062] The nitrile monomer may be, for example, an alkenyl cyanide, and specifically may be one or more monomers selected from the group consisting of acrylonitrile, methacrylonitrile, and allyl cyanide, but is not limited thereto.

[0063] Examples of the (Group III) unsaturated carboxylic acid monomer include, but are not limited to, one or more monomers selected from the group consisting of maleic acid, fumaric acid, methacrylic acid, acrylic acid, glutaconic acid, itaconic acid, tetrahydrophthalic acid, crotonic acid, isocrotonic acid, and nadic acid.

[0064] More preferably, the core portion of the emulsion polymer particle A having the above-mentioned core-shell structure may contain all of the polymers of (group A) conjugated diene monomers or conjugated diene polymers, (group B) vinyl monomers, and (group C) unsaturated carboxylic acid monomers.

[0065] As a more preferred example, the core portion of the emulsion polymer particle A having the above-mentioned core-shell structure may contain a polymer of monomers or polymers in which the above-mentioned (group A) monomer or polymer is contained in the range of 30 to 70 wt %, the above-mentioned (group B) monomer is contained in the range of 20 to 50 wt %, and the above-mentioned (group C) unsaturated carboxylic acid monomer is contained in the range of 0.5 to 20 wt %, based on the total weight of the core portion.

[0066] As a more preferred example, the core of the emulsion polymer particles A having the core-shell structure may be styrene-butadiene latex. The binder composition for secondary batteries of the present invention contains the emulsion polymer particles having the core-shell structure, thereby enabling the optimum effect of the present invention to be achieved.

[0067] As a more preferred example, the shell portion of the emulsion polymer particle A having the core-shell structure may include a polymer of one or more monomers selected from the group consisting of (group A) (meth)acrylic acid ester monomers, (group B) acrylic monomers, vinyl monomers, (meth)acrylamide monomers, and nitrile monomers, and (group C) unsaturated carboxylic acid monomers.

[0068] Examples of the (meth)acrylic acid ester monomer (group A) include, but are not limited to, one or more monomers selected from the group consisting of allyl methacrylate, methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, n-amyl acrylate, isoamyl acrylate, n-ethylhexyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-amyl methacrylate, isoamyl methacrylate, n-hexyl methacrylate, n-ethylhexyl methacrylate, 2-ethylhexyl methacrylate, lauryl acrylate, ceryl acrylate, stearyl acrylate, lauryl methacrylate, cetyl methacrylate, and stearyl methacrylate.

[0069] The monomers of (group B) and (group C) are as exemplified for the core portion of the emulsion polymer particles A having a core-shell structure, but are not limited thereto.

[0070] More preferably, the shell portion of the emulsion polymer particle A having the above-mentioned core-shell structure may contain all of the polymers of (group A) (meth)acrylic acid ester monomers, (group B) vinyl monomers, and (group C) unsaturated carboxylic acid monomers.

[0071] As a more preferred example, the shell portion of the emulsion polymer particle A having the above core-shell structure may comprise a polymer of monomers in which the above (group A) monomer is contained in an amount of 50 to 90% by weight, the above (group B) monomer is contained in an amount of 0.5 to 30% by weight, and the above (group C) unsaturated carboxylic acid monomer is contained in an amount of 0.5 to 20% by weight, based on the total weight of the shell portion.

[0072] In the present invention, the binder composition for secondary batteries may further contain an antioxidant and a preservative. In particular, when the binder for secondary batteries of the present invention is used, an antioxidant may be preferably used to reduce deterioration.

[0073] In addition, the binder composition for a secondary battery may further include one or more substances selected from the group consisting of a viscosity modifier and a filler, which will be described in detail below.

[0074] An electrode mixture for a secondary battery according to an embodiment of the present invention includes the binder composition for a secondary battery and an electrode active material capable of absorbing and releasing lithium.

[0075] The electrode mixture for a secondary battery may further include a conductive material, which will be described in detail below.

[0076] A secondary battery according to an embodiment of the present invention includes an electrode for a secondary battery including the electrode mixture for a secondary battery. The electrode for a secondary battery may be manufactured by applying the electrode mixture on a current collector, drying and rolling the electrode mixture. The electrode for a secondary battery may be a positive electrode or a negative electrode.

[0077] The positive electrode is manufactured, for example, by applying a mixture of a positive electrode active material, a conductive material, a binder, etc., onto a positive electrode current collector and then drying the mixture, and the negative electrode is manufactured, for example, by applying a mixture of a negative electrode active material, a conductive material, a binder, etc., onto a negative electrode current collector and then drying the mixture. In some cases, the negative electrode may not contain a conductive material.

[0078] The positive electrode active material contains two or more transition metals as a lithium transition metal oxide, for example, lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ), lithium manganese oxides substituted with one or more transition metals; chemical formula LiNi 1-y M y O 2 (wherein M=Co, Mn, Al, Cu, Fe, Mg, B, Cr, Zn or Ga, and contains one or more of the above elements, and 0.01≦y≦0.7); Li 1+z Ni 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 , Li 1+z Ni 0.4 Mn 0.4 Co 0.2 O 2 Li 1+z Ni b Mn c Co 1-(b+c+d) M d O (2-e) A e (wherein, -0.5≦z≦0.5, 0.1≦b≦0.8, 0.1≦c≦0.8, 0≦d≦0.2, 0≦e0.2, b+c+d<1, M=Al, Mg, Cr, Ti, Si, or Y, and A=F, P, or Cl); Lithium nickel cobalt manganese composite oxide represented by the formula Li 1+x M 1-y M' y PO 4-z X z(wherein M=transition metal, preferably Fe, Mn, Co, or Ni; M′=Al, Mg, or Ti; X=F, S, or N; −0.5≦x≦+0.5; 0≦y≦0.5; 0≦z≦0.1).

[0079] Examples of the negative electrode active material include carbon and graphite materials such as natural graphite, artificial graphite, expanded graphite, carbon fiber, non-graphitizable carbon, carbon black, carbon nanotubes, fullerenes, and activated carbon; metals such as Al, Si, Sn, Ag, Bi, Mg, Zn, In, Ge, Pb, Pd, Pt, and Ti that can be alloyed with lithium and compounds containing such elements; composites of metals and their compounds with carbon and graphite materials; lithium-containing nitrides, etc. Among them, carbon-based active materials, silicon-based active materials, tin-based active materials, and silicon-carbon-based active materials are more preferable, and these may be used alone or in combination of two or more, but are not limited to these.

[0080] The conductive material is a component for further improving the conductivity of the electrode active material, and may be added in the range of 0.01 to 30% by weight based on the total weight of the electrode mixture. Such a conductive material is not particularly limited as long as it has conductivity that does not cause chemical changes in the battery, and examples thereof include graphite such as natural graphite and artificial graphite; carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; carbon derivatives such as carbon nanotubes and fullerenes, conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0081] In the above-mentioned electrodes, the current collector is a site where electrons move due to an electrochemical reaction of the active material, and there are positive electrode current collectors and negative electrode current collectors depending on the type of electrode.

[0082] The positive electrode current collector is generally formed to a thickness of 3 to 500 μm. Such a positive electrode current collector is not particularly limited as long as it has high conductivity and does not cause chemical changes in the battery, and examples thereof include stainless steel, aluminum, nickel, titanium, baked carbon, and aluminum or stainless steel whose surface is surface-treated with carbon, nickel, titanium, silver, etc.

[0083] The negative electrode current collector is generally formed to a thickness of 3 to 500 μm. Such a negative electrode current collector is not particularly limited as long as it has conductivity that does not cause a chemical change in the battery, and examples thereof include copper, stainless steel, aluminum, nickel, titanium, plastic carbon, copper or stainless steel whose surface is surface-treated with carbon, nickel, titanium, silver, etc., and aluminum-cadmium alloy.

[0084] These current collectors can have fine irregularities formed on their surfaces to strengthen the bonding strength of the electrode active material, and can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and nonwoven fabrics.

[0085] The mixture (electrode mixture) of the electrode active material, conductive material, binder, and the like may further contain one or more substances selected from the group consisting of a viscosity modifier and a filler.

[0086] The viscosity regulator is a component that adjusts the viscosity of the electrode mixture so that the electrode mixture can be mixed and applied to the current collector with ease, and may be added in an amount of up to 30% by weight based on the total weight of the electrode mixture. Examples of such viscosity regulators include, but are not limited to, carboxymethyl cellulose, polyacrylic acid, etc.

[0087] The filler is an auxiliary component that suppresses the expansion of the electrode, and is not particularly limited as long as it is a fibrous material that does not cause chemical changes in the battery. Examples of the filler include olefin polymers such as polyethylene and polypropylene; and fibrous substances such as glass fiber and carbon fiber.

[0088] The secondary battery of the present invention may further include a separator and a lithium salt-containing non-aqueous electrolyte in addition to the electrodes.

[0089] As the separator, an insulating thin film having high ion permeability and mechanical strength is used, which is interposed between the positive electrode and the negative electrode. The pore diameter of the separator is generally 0.01 to 10 μm, and the thickness is generally 5 to 300 μm. As such a separator, for example, a sheet or nonwoven fabric formed of an olefin polymer such as polypropylene, which is chemically resistant and hydrophobic, glass fiber, or polyethylene, etc. is used. When a solid electrolyte such as a polymer is used as the electrolyte, the solid electrolyte can also serve as the separator.

[0090] The lithium salt is easily soluble in the non-aqueous electrolyte, and examples of the lithium salt include LiCi, LiBr, LiI, and LiClO. 4 , LiBF 4 , LiB 10 Cl 10 , LiPF 6 , LiCF 3 SO 3 , LiCF 3 CO 2 , LiAsF 6 , LiSbF 6 , LiAlCl 4 , C.H. 3 SO 3 Li, (CF 3 SO 2 ) 2 Examples of the lithium borane include, but are not limited to, NLi, lithium chloroborane, lithium lower aliphatic carboxylate, lithium 4-phenylborate, imides, and the like.

[0091] Examples of the non-aqueous electrolyte include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydroxyfuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate, but are not limited thereto.

[0092] In another embodiment, an organic solid electrolyte, an inorganic solid electrolyte, etc. may be used.

[0093] Examples of the organic solid electrolyte that can be used include polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyagitation lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, and polymers containing ionic dissociable groups.

[0094] The inorganic solid electrolyte is, for example, Li 3 N, LiI, Li 5 NI 2 , Li 3 N-LiI-LiOH, LiSiO 4 , LiSiO 4 -LiI-LiOH, Li 2 SiS 3 , Li 4 SiO 4 , Li 4 SiO 4 -LiI-LiOH, Li 3 PO 4 -Li 2 S-SiS 2Nitrides, halides, and sulfates of Li such as these are used.

[0095] The lithium secondary battery according to the present invention can be used as a battery cell to serve as a power source for small devices, and can also be used as a single cell in a medium- to large-sized battery module made up of multiple battery cells.

[0096] The present invention will be described in detail below with reference to examples and experimental examples, but the present invention is not limited to these examples.

[0097] <Production Example of Emulsion Polymer Particles> Production Example 1: Production of emulsion polymer particles A1 having a core-shell structure First polymerization: formation of the core As monomers for forming the core, 50 g of 1,3-butadiene, 35 g of styrene, 10 g of methyl methacrylate, and 5 g of a mixture of acrylic acid and itaconic acid in a ratio of 5:5 were used.

[0098] As a solvent, about 400 parts by weight of water was used relative to a total of 100 parts by weight of the monomer components.

[0099] Water, the above-mentioned monomers, and about 3 parts by weight of sodium lauryl sulfate as an emulsifier component per 100 parts by weight of the monomer components were added to a polymerization reactor purged with nitrogen, and the temperature was raised to about 75°C. Then, 0.005 mol of potassium persulfate was added as a polymerization initiator to start emulsion polymerization.

[0100] While maintaining the temperature at about 75° C., the polymerization reaction was carried out for about 7 hours to obtain an emulsion-type binder.

[0101] Second polymerization: shell formation As additional monomers for forming the shell, 69.9 g of n-butyl acrylate, 20.0 g of styrene, 10 g of methacrylic acid, and 0.1 g of allyl methacrylate were used, and 933.3 g (233.33 g based on the solid content) of the emulsion of the emulsion polymer particles obtained in Production Example 1 was used.

[0102] Into a polymerization reactor substituted with nitrogen, water, the above-mentioned monomers, the latex particle cores obtained by the first polymerization, and about 0.2 parts by weight of sodium polyoxyethylene lauryl ether sulfate as an emulsifier component relative to a total of 100 parts by weight of the monomer components were charged, and while maintaining the temperature at about 80°C, 0.33 parts by weight of ammonium persulfate as a polymerization initiator relative to 100 parts by weight of the monomer components was charged to start emulsion polymerization.

[0103] The reaction was carried out for about 5 hours while maintaining the temperature at about 80°C, and an emulsion-type binder containing emulsion polymer particles having a core-shell structure was obtained (average particle size: 70 nm).

[0104] The pH was adjusted to 7 with aqueous sodium hydroxide.

[0105] Production Example 2: Production of emulsion polymer particles A2 having a core-shell structure Emulsion polymer particles A2 having a core-shell structure were produced in the same manner as in Production Example 1, except that in the second polymerization (formation of the shell portion) in Production Example 1, 69.9 g of n-butyl acrylate, 25.0 g of styrene, 5 g of methacrylic acid, and 0.1 g of allyl methacrylate were used as monomers for forming the shell (average particle size: 71 nm).

[0106] Production Example 3: Production of emulsion polymer particles A3 having a core-shell structure In the first polymerization in Production Example 1, the content of the emulsifier was reduced, and the average particle size (D50) was changed as shown in Table 1 below to produce emulsion polymer particles A3 having a core-shell structure. (Average particle size: 102 nm)

[0107] Production Example 4: Production of emulsion polymer particles A4 having a core-shell structure Emulsion polymer particles A4 having a core-shell structure were produced in the same manner as in Production Example 1, except that 34 g of 1,3-butadiene, 51 g of styrene, 10 g of methyl methacrylate, and 5 g of a mixture of acrylic acid and itaconic acid in a 5:5 ratio were used as the monomers for the first polymerization (core portion) in Production Example 1. (Average particle size: 73 nm)

[0108] Production Example 5: Production of emulsion polymer particles B1 As monomers, 56.8 g of 1,3-butadiene, 38.5 g of styrene, 3 g of methyl methacrylate, and 1.7 g of a mixture of acrylic acid and itaconic acid in a ratio of 5:5 were used.

[0109] As a solvent, about 150 parts by weight of water was used relative to a total of 100 parts by weight of the monomer components.

[0110] Water, the above-mentioned monomers, and about 1 part by weight of sodium lauryl sulfate as an emulsifier component per 100 parts by weight of the monomer components were charged into a nitrogen-substituted polymerization reactor, and the temperature was raised to about 75°C. Then, 0.005 mol of potassium persulfate was added as a polymerization initiator to start emulsion polymerization.

[0111] The polymerization reaction was carried out for about 10 hours while maintaining the temperature at about 75°C, and after the reaction was completed, about 0.5 parts by weight of sodium lauryl sulfate was added as a stabilizing emulsifier to obtain an emulsion-type binder (average particle size: 261 nm).

[0112] The pH was adjusted to 7 with aqueous sodium hydroxide.

[0113] Production Example 6: Production of emulsion polymer particles B2 Emulsion polymer particles B2 were produced by decreasing the amount of 1,3-butadiene added in Production Example 5, increasing the content of styrene, and changing the glass transition temperature (Tg) as shown in Table 1 below. (Average particle size: 262 nm)

[0114] Production Example 7: Production of emulsion polymer particles B3 In Production Example 5, an increased amount of sodium lauryl sulfate was added to produce emulsion polymer particles B3 having an average particle size of 184 nm.

[0115] Experimental Example 1: Evaluation of the average particle size, glass transition temperature (Tg) and gel content of emulsion polymer particles The average particle size (D50), glass transition temperature (Tg) and gel content (%) of the emulsion polymer particles produced in Production Examples 1 to 7 above were measured by the methods described below, and the results are shown in Table 1 below.

[0116] Measurement of average particle size (D50) A sample diluted to 200 ppm or less was prepared, and the average particle size (D50) was measured at room temperature (23°C) using Nicomp380 according to the intensity Gaussian distribution by dynamic laser light scattering.

[0117] Glass transition temperature (Tg) measurement The measurements were carried out using a Differential Scanning Calorimetry (DSC).

[0118] Gel content determination After drying the emulsion polymer particle sample at 80°C for 24 hours, about 0.5 g was taken and the weight was measured. a Next, the sample of emulsion polymer particles whose weight was measured was immersed in 50 g of THF (tetrahydrofuran) for 24 hours. Next, the emulsion polymer particle sample contained in THF was sieved through a 200 mesh sieve whose weight was known, and the weight of the mesh and the emulsion polymer remaining on the mesh were measured, and the weight of the 200 mesh was subtracted from this value to obtain the weight M of the emulsion polymer remaining on the mesh. b The M measured according to the above method a and M b The gel content was calculated by substituting the above into the following [Equation 1]. At this time, the gel content of each emulsion polymer particle was measured three or more times for each sample, and the average value was calculated.

[0119] [Mathematical formula 1] Gel content = M b / M a *100

[0120] [Table 1]

[0121] Examples 1 to 3 and Comparative Examples 1 to 6 Manufacturing of mixed binders The emulsion polymer particles produced above were mixed in the particle number ratios shown in Table 2 below to produce mixed binders according to Examples 1 to 3 and Comparative Examples 1 to 6.

[0122] Electrode Slurry and Electrode Production Using water as a dispersion medium, artificial graphite (95.5 g), acetylene black (1 g), the mixed binders (2.5 g) prepared in Examples 1 to 3 and Comparative Examples 1 to 6, and carboxymethyl cellulose (1 g) as a thickener were mixed based on 100 g of total solids, so that the total solids content was 48 wt % to prepare a slurry for the negative electrode. The slurry was applied to a copper foil in a thickness of 200 μm, and then vacuum dried and pressed to prepare a negative electrode.

[0123] Experimental Example 2: Evaluation of adhesive strength of mixed binder and color difference meter value after pressing The adhesive strength (gf / cm) and the L value of a color difference meter after pressing of the mixed binders produced in Examples 1 to 3 and Comparative Examples 1 to 6 were measured by the methods described below. The results are shown in Table 2 below.

[0124] N(A) / N(B) Determination A sample diluted to 200 ppm or less was prepared, and the average particle size (D50) was measured at room temperature (23°C) using a Nicomp380 dynamic laser light scattering method according to the intensity Gaussian distribution, and then N(A) / N(B) was determined based on the following [Relationship 2].

[0125] [Equation 2] N(A) / N(B)={D(B) / (D)A} 3 *{X(A) / X(B)}

[0126] In the above [Relationship 2], D(A) is the average particle size (D50) of particle A, D(B) is the average particle size (D50) of particle B, and X(A) / X(B) is the mixing ratio of A to B.

[0127] Measurement of adhesive strength (gf / cm) The negative electrode plate was cut to a certain size and placed on a slide glass, after which the current collector was removed and the 180 degree peel strength was measured and averaged.

[0128] Colorimeter measurements This experiment was carried out to evaluate the change in the color difference meter value due to the occurrence of contamination caused by roll adhesion during the rolling process for each electrode manufactured in the examples and comparative examples.

[0129] Specifically, the press roll may be contaminated during the process of rolling the coated negative electrode (that is, the negative electrode slurry is applied to the current collector and then dried) with a roll press.

[0130] At this time, when a color difference meter is applied to the surface of the press roll and measured, if the press roll is very clean, the value will be 80, but as the press roll becomes contaminated, the value will decrease, and if the press roll is actually contaminated in the same way as the electrode surface, the value may drop to as low as 40. In relation to this, after each rolling process in Examples 1 to 3 and Comparative Examples 1 to 6, the press roll surface was measured with a color difference meter.

[0131] [Table 2]

[0132] As can be seen from Table 2, in Comparative Examples 1, 3, and 6, in which the N(A) / N(B) value was outside the range of more than 50 and less than 400, it was confirmed that the L value of the color difference meter after pressing was significantly reduced to 60 or less. In particular, it was confirmed that in Comparative Example 1, defects occurred on the electrode surface, and in Comparative Example 6, detachment of the electrode occurred.

[0133] In particular, Comparative Example 3, in which the average particle size (D50) of the emulsion polymer particles A exceeds 100 nm, was confirmed to have the lowest L value of 46 on the colorimeter after pressing among Comparative Examples 1, 3 and 6, in which the N(A) / N(B) value falls outside the range of more than 50 and less than 400.

[0134] In addition, in Comparative Example 4, in which the glass transition temperature (Tg) of the emulsion polymer particles A was 0°C or higher, the adhesive strength was significantly reduced to 41 gf / cm, and the L value of the color difference meter after pressing was 69, which was confirmed to be slightly lower.

[0135] In Comparative Example 5, in which the glass transition temperature (Tg) of the emulsion polymer particles B was 0° C. or higher, the adhesive strength was significantly reduced to 35 gf / cm, and the L value of the color difference meter after pressing was significantly reduced to 58. Furthermore, it was confirmed that the electrodes were detached.

[0136] In contrast, in Examples 1, 2, and 3, in which the N(A) / N(B) value was within the range of more than 50 and less than 400, the average particle size (D50) of the emulsion polymer particles A was 100 nm or less, the glass transition temperature (Tg) of the emulsion polymer particles A was less than 0°C, and the glass transition temperature (Tg) of the emulsion polymer particles B was less than 0°C, it was confirmed that not only did the adhesive strength remain high and the L value of the color difference meter after pressing was excellent at 78, but also that the electrodes had excellent physical properties without any defects.

Claims

1. The emulsion polymer particles A have a core-shell structure including a core and a shell occupying a part or all of the surface of the core, and the emulsion polymer particles B do not have a core-shell structure, A binder composition for a secondary battery, which satisfies the following [Relationship 1]: [Relationship 1] 50<N(A) / N(B)<400 (In the formula, N(A) is the number of emulsion polymer particles A having the above-mentioned core-shell structure, N(B) is the number of emulsion polymer particles B not having the above-mentioned core-shell structure, and N(A) / N(B) is determined by the following [Relationship 2].) [Relationship 2] N(A) / N(B)={D(B) / D(A)} 3 *{X(A) / X(B)} (In the formula, D(A) is the average particle size (D50) of particle A, D(B) is the average particle size (D50) of particle B, and X(A) / X(B) is the mixing ratio of A to B.)

2. 2. The binder composition for a secondary battery according to claim 1, wherein the emulsion polymer particles A having a core-shell structure have an average particle size (D50) of 100 nm or less.

3. 2. The binder composition for a secondary battery according to claim 1, wherein all of the polymer particles contained in the binder composition for a secondary battery have an average particle size (D50) of 400 nm or less.

4. 2. The binder composition for a secondary battery according to claim 1, wherein the glass transition temperature (Tg) of the emulsion polymer particle A having a core-shell structure is lower than 0°C.

5. 2. The binder composition for a secondary battery according to claim 1, wherein the glass transition temperature (Tg) of the emulsion polymer particle B not having a core-shell structure is lower than 0°C.

6. The core portion of the emulsion polymer particle A having the core-shell structure is (Group A) Conjugated diene monomers or conjugated diene polymers, (Group B) one or more monomers selected from the group consisting of acrylate monomers, vinyl monomers, (meth)acrylamide monomers, and nitrile monomers; and (Group C) Unsaturated carboxylic acid monomers, The binder composition for a secondary battery according to claim 1 , comprising a polymer of one or more monomers or polymers selected from the following:

7. 7. The binder composition for a secondary battery according to claim 6, wherein the core portion of the emulsion polymer particle A having a core-shell structure comprises a polymer of monomers or polymers, the monomers or polymers being contained in the range of 30 to 70 wt % of the (A) group, the monomers being contained in the range of 20 to 50 wt % of the (B) group, and the unsaturated carboxylic acid monomers being contained in the range of 0.5 to 20 wt % of the (C) group, relative to the total weight of the core portion.

8. 2. The binder composition for a secondary battery according to claim 1, wherein the core of the emulsion polymer particle A having a core-shell structure contains styrene-butadiene latex.

9. The shell portion of the emulsion polymer particle A having the core-shell structure is (Group A) (meth)acrylic acid ester monomers, (Group B) one or more monomers selected from the group consisting of acrylate monomers, vinyl monomers, (meth)acrylamide monomers, and nitrile monomers; and (Group C) Unsaturated carboxylic acid monomers, The binder composition for a secondary battery according to claim 1 , comprising a polymer of one or more monomers or polymers selected from the following:

10. 10. The binder composition for a secondary battery according to claim 9, wherein the shell portion of the emulsion polymer particle A having a core-shell structure comprises a polymer of monomers, the polymer comprising the (A) monomer in an amount of 50 to 90 wt %, the (B) monomer in an amount of 0.5 to 30 wt %, and the (C) unsaturated carboxylic acid monomer in an amount of 0.5 to 20 wt %, based on the total weight of the shell portion.

11. An electrode mixture for a secondary battery, comprising the binder composition for a secondary battery according to claim 1 .

12. A secondary battery comprising the electrode mixture for a secondary battery according to claim 11.

Citation Information

Patent Citations

  • Composition for nonaqueous secondary battery adhesive layer, adhesive layer for nonaqueous secondary battery, and nonaqueous secondary battery

    JP2017098203A

  • Composition for nonaqueous secondary battery functional layers, functional layer for nonaqueous secondary batteries, and nonaqueous secondary battery

    WO2018096975A1

  • Binder composition for nonaqueous secondary battery porous film, slurry composition for nonaqueous secondary battery porous film, and nonaqueous secondary battery porous film, nonaqueous secondary battery and production method therefor

    WO2018198940A1